Câu 1 tính A (-15)+14+(-85) Câu 2 tìm x a 12x-64=2^5 b x-7=(-14)+(-8) Câu 3 Cho S =1+2+2^2+2^3+2^4+2^5+2^6+2^7

Question

Câu 1 tính
A (-15)+14+(-85)
Câu 2 tìm x
a 12x-64=2^5
b x-7=(-14)+(-8)
Câu 3
Cho S =1+2+2^2+2^3+2^4+2^5+2^6+2^7

in progress 0
Mary 3 ngày 2021-12-06T23:34:54+00:00 2 Answers 3 views 0

Answers ( )

    0
    2021-12-06T23:36:47+00:00

    Đáp án:

    `a) (-15)+14+(-85)=[(-15)+(-85)]+14=-100+14=-86`

    `——`

    `12x-64=2^5 `

    `-> 12x-64=32`

    `-> 12x=32+64=96`

    `-> x=96:12=8`

    `—–`

    `x-7=(-14)+(-8)`

    `-> x-7=-22`

    `-> x=-22+7`

    `-> x=-15`

    `—–`

    `S =1+2+2^2+2^3+2^4+2^5+2^6+2^7`

    `=(1+2)+(2^2+2^3)+(2^4+2^5)+(2^6+2^7)`

    `=3+2^2(1+2)+2^4(1+2)+2^6(1+2)`

    `=3+2^2. 3+2^4. 3+2^6. 3`

    `=3(1+2^2+2^4+2^6) vdots 3`

    0
    2021-12-06T23:36:53+00:00

    Đáp án:

    Câu 1:

    A= (-15)+14+(-85)

    A=(-1) + (-85)

    A=(-86)

    Câu 2:

    a, 12x – 64 =2^5

        12x – 64 = 32

        12x      = 32+64
        12x      = 96

           x       = 96:12

           x       = 8

     Vậy x = 8

    b,x-7= (-14)+(-8)

       x-7= (-22)

       x    = (-22)+7

       x    = (-15)

     Vậy x = (-15)

    Câu 3:

    S = 1+2+2^2+2^3+2^4+2^5+2^6+2^7

    S = (1+2) +2^2×(1+2^1)+2^4×(1+2^1)+2^6×(1+2^1)

    S = 3 × 1+ 2^2 × 3 +2^4 ×3 + 2^6 × 3

    S = 3 × (1+2^2 + 2^4 + 2^6) chia hết cho 3

    Hay S =( 1+2+2^2+2^3+2^4+2^5+2^6+2^7 )  chia hết cho 3

    Vậy S =( 1+2+2^2+2^3+2^4+2^5+2^6+2^7 )  chia hết cho 3

Leave an answer

Browse

35:5x4+1-9:3 = ? ( )